Disentangling development of sensation seeking, risky peer affiliation, and binge drinking in adolescent sport - Drane, Catherine; Modecki, Kathryn; Barber, Bonnie (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Binge drinking is pervasive among adolescents and is an important public health concern. Research suggests that approximately 14% of US adolescents have been drunk in the past month and 17% of Australian adolescents binge drink on a monthly basis (Australian Institute of Health and Welfare, 2011, Johnston et al., 2012). Generally, binge drinking increases during adolescence and this increase is particularly troublesome given links between adolescent binge drinking and later alcohol-related problems (Kwan, Cairney, Faulkner, & Pullenayegum, 2012). Further, continued alcohol abuse is associated with negative physical and mental health consequences, such as coronary heart disease, aggression, and mood disorders (Brook, Cohen, & Brook, 1998). For this reason, identifying developmental factors that predict increases in binge drinking during adolescence is imperative.